PERCENTAGE OF CARCASS PARTS OF BROILER CHICKEN GIVEN ADDITIONAL AFRICAN LEAF FLOUR FEED (VERNONIA AMYGDALINA) - Badaruddin R.; Auza F.A.; Syamsuddin; Sandiah N.; Munadi L.M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Feed is an important thing in supporting the broiler farming business and currently, research on natural feed ingredients as animal feed additives has been widely carried out by researchers and breeders, one of which is African leaves. This study aimed to analyze the carcass of broiler chickens fed with African leaf meal (Vernonia amygdalina) at different levels using 100 broiler chicks a day (DOC) strain SR 202 with a trial period and maintenance of 5 weeks using a completely randomized design (CRD) with 4 treatments and 5 replications. Each replication consisted of 5 chickens with feed in the form of CAB broiler concentrate feed, milled corn, bran, and African leaf flour mixed according to the needs in the treatment. The results showed the average percentage of broiler chicken breast pieces ranged from 35,89-37,18%, thigh weight ranged from 27,98-30,16%, wing pieces 11,36-11,61% and back weight percentage was 20,96-22,31%.